On q-Euler Numbers Related to the Modified q-Bernstein Polynomials - Min-Soo Kim; Daeyeoul Kim; Taekyun Kim (Abstract and Applied Analysis)
We consider q-Euler numbers, polynomials, and q-Stirling numbers of first and second kinds. Finally, we investigate some interesting properties of the modified q-Bernstein polynomials related to q-Euler numbers and q-Stirling numbers by using fermionic p-adic integrals on ℤp.